2021
DOI: 10.56093/ijans.v90i8.109207
|View full text |Cite
|
Sign up to set email alerts
|

Precision dairy farming: Opportunities and challenges for India

Abstract: Effective management of a dairy farm has to focus on individual animal apart from group or herd management since 'smallest production unit in the dairy is the individual animal’. In this context, precision dairy farming (PDF) aims to manage the basic production unit in order to exploit its maximal production capacity. PDF is the use of information and technology based farm management system to measure physiological, behavioural and production indicators of individual animals to improve management strategies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In addition, Eastwood et al [11] identified a moral dilemma in the ethics of such precision technology devices that could spark societal discussions about animal welfare. Apart from the factors that influence the adoption of RFID like education of farmers, knowledge, age, farm size, business complexity, ownership, risk perception etc., Rathod and Dixit [12] highlighted several challenges in the adoption of such precision technology, like the incapability to assess cost-effectiveness, chances of technical failures due to high degree of automation, dependence upon technically sound and skilled workforce to access, interpret and analyze the generated data. Overall awareness, affordability and socio-cultural beliefs have been found the most prominent challenges in the adoption of digital devices such as RFID-based cow collars in India, because, most of the livestock is scattered by low-holding farmers in remote village areas where, even for the basic necessity, the population has to travel long distances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Eastwood et al [11] identified a moral dilemma in the ethics of such precision technology devices that could spark societal discussions about animal welfare. Apart from the factors that influence the adoption of RFID like education of farmers, knowledge, age, farm size, business complexity, ownership, risk perception etc., Rathod and Dixit [12] highlighted several challenges in the adoption of such precision technology, like the incapability to assess cost-effectiveness, chances of technical failures due to high degree of automation, dependence upon technically sound and skilled workforce to access, interpret and analyze the generated data. Overall awareness, affordability and socio-cultural beliefs have been found the most prominent challenges in the adoption of digital devices such as RFID-based cow collars in India, because, most of the livestock is scattered by low-holding farmers in remote village areas where, even for the basic necessity, the population has to travel long distances.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These demand-led information deliveries facilitated disease prevention and improved animal health, resulting in time, labour, and financial savings for this marginalised population. Various information kiosks developed by veterinary organisations are Information Kiosk on Dairy Management, CVAS, Mannuthy; The Livestock Guru, Orissa; Dairy Information System Kiosk(DISK), Anand; Information Kiosk on Livestock Production Management-SVVU [38][39][40][41].…”
Section: Touch Screen Information Kioskmentioning
confidence: 99%